PENGARUH BRAND POSITIONING PUSPA IPTEK SUNDIAL TERHADAP KEPUTUSAN BERKUNJUNG DI KOTA BARU PARAHYANGAN (Survei Pada Wisatawan Nusantara yang Berkunjung ke Puspa Iptek Sundial) - Atthauri, Hibban; Purnama, Ridwan (THE Journal : Tourism and Hospitality Essentials Journal, 2015)
Tourism industries in Indonesia has developed very advanced, this is due to the increasing number of tourists both foreign tourists and domestic tourists. The development of the need for care and maintenance as well as improvement in various sectors, especially regarding the facility and to provide easy of accommodation for tourists visiting. Puspa Iptek Sundial is one of the tourist attraction located in the area Kota Baru Parahyangan West Bandung regency, it is easy to access and make it as a choice of tourist attraction to visit. The implementation of Brand Positioning in this study measured by the knowledge of respondents to Attributes, Benefits and Beliefs and Value. Respondents also being questioned on their perception about visiting decision to the Puspa Iptek Sundial. The results of this study indicate that the Brand positioning influence on decision to visit. This can be seen from the significantly high level of correlation and also the result shows the relationship between Brand Positioning and against visiting decision is in a strong relationship.